Antibacterial Test of Ziziphus spina-christi (L.) Desf. Leaves Extract Againstgram-Positive Bacteria - Feskaharny Alamsjah; Anthoni Agustien; Fadhila Cantika (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Ziziphus spina-christi (L.) Desf. is a member of the Rhamnaceae family, which has efficacy values as herbal plants used in traditional medicines. The spread of infectious diseases in humans has increased in recent years, raising public awareness of the importance of using traditional medicine as the first line of prevention against infectious diseases. This research aimed to determine the antibacterial activity of fresh extract, infusion, and ethanol extract and to determine the greatest inhibition zone of Z. spina-christi leaves against Gram-positive bacteria (B. cereus, B. subtilis, S. aureus, and S. epidermidis). This research used the survey method with a purposive sampling technique. The results showed that fresh extract, infusion, and ethanol extract of the Z. spina-christi leaves had antibacterial activity against Gram-positive bacteria (B. cereus, B. subtilis, S. aureus, and S. epidermidis) and the greatest inhibition zone was obtained from the ethanol extract with a strong inhibition category.